Kesiapan Prosedur Pembelajaran Tatap Muka pada Masa Pandemi Covid-19 di Kelas Rendah SD Muhammadiyah Geger Bantul - Rifki Lukma Vita, Nanda; Awalia Putri, Mufida; Ardiyaningrum, Martalia; Syamsul Arifin, Ahmad (Indonesian Journal of Islamic Elementary Education, 2022)
Covid-19 cases began to decrease, schools were encouraged to carry out face-to-face learning. Therefore the government has issued several procedures related to schools that will implement Face-to-Face Learning (PTM). This study aims to 1) find out the procedures that have been prepared for the implementation of PTM and 2) find out the procedures for implementing PTM at SD Muhammadiyah Geger. This research is a qualitative research, the type of research is descriptive qualitative. The subjects of this study consisted of school principals, teachers of lower grades (grade 1 SD), lower grades, and lower grades' guardians. Taking the subject of low grade students and guardians of low grade students were grouped into three levels (high, medium and low). Data collection techniques from students about procedure readiness using a questionnaire. For low school principals and homeroom teachers using interview, observation, and documentation techniques. Data analysis techniques include data reduction, data presentation and drawing conclusions. The results of this study indicate that the procedures that have been prepared by SD Muhammadiyah Geger in face-to-face learning as a whole have been running in accordance with the SKB 4 Ministers rules such as spraying disinfectants, checking temperature, washing hands, maintaining distance, and making sure that each teacher and student has injected with the vaccine and when going to school must be in good health. The implementation of face-to-face learning (PTM) procedures at Muhammadiyah Geger Elementary School has been going well. This can be seen from the results of the research which stated that teachers, students and guardians of SD Muhammadiyah Geger students were very ready to carry out face-to-face learning by complying withthe procedures that had been made. However, there are several aspects that need improvement, especially teachers who are not used to wearing masks in the school environment, students who have not been vaccinated at least twice, and students who are reluctant to bring their own food to school.